Cross-laminated Timber (CLT) in China: A State-of-the-Art - Hao Li; Brad Jianhe Wang; Peixing Wei; Libin Wang (Journal of Bioresources and Bioproducts, 2019)
As a new type of green low-carbon engineered wood product, cross-laminated timber (CLT) is widely used in various types of wooden buildings in Europe and North America, and the number of high-rise wood construction is also increasing. Based on the introduction of the structural characteristics of the CLT and the development status of the CLT in developed countries, this paper focused on the review of the status of research and development of the CLT in China, with an emphasis on the breakthrough technologies of new bamboo-wood composite CLT developed. Finally, the prospects of the CLT in China were discussed.